A Novel RNA Aptamer as Synthetic Inducer of DasR Controlled Transcription - Vockenhuber, Michael Paul; Hoetzel, Janis; Maurer, Lisa Marie; Fröhlich, Philipp; Weiler, Sigrid; Muller, Yves; Koeppl, Heinz; Suess, Beatrix (ACS Synthetic Biology, 2024)
Progress in the synthetic biology field is driven by the development of new tools for synthetic circuit engineering. Traditionally, the focus has relied on protein-based designs. In recent years, the use of RNA-based tools has tremendously increased, due to their versatile functionality and applicability. A promising class of molecules is RNA aptamers, small, single-stranded RNA molecules that bind to a target molecule with high affinity and specificity. When targeting bacterial repressors, RNA aptamers allow one to add a new layer to an established protein-based regulation. In the present study, we selected an RNA aptamer binding the bacterial repressor DasR, preventing its binding to its operator sequence and activating DasR-controlled transcription in vivo. This was made possible only by the combination of an in vitro selection and subsequent in vivo screening. Next-generation sequencing of the selection process proved the importance of the in vivo screening for the discovery of aptamers functioning in the cell. Mutational and biochemical studies led to the identification of the minimal necessary binding motif. Taken together, the resulting combination of bacterial repressor and RNA aptamer enlarges the synthetic biology toolbox by adding a new level of regulation.
CRIS-Team Scopus Importer:2024-02-23
Keywords: bacterial repressor; DasR; gene regulation; in vitro selection; RNA aptamer; SELEX